2017
DOI: 10.1515/aopf-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein on the growth of mullet, Chelon labrosus, reared in sea cages

Abstract: Abstract. The purpose of the study was to obtain preliminary data on the effect of dietary protein on the growth of the thick-lipped grey mullet (Chelon labrosus) juveniles reared in net sea-cages. The juveniles (6.2 ± 0.61 g) were obtained from the wild and were stocked into net sea-cages at a stocking rate of 100 juveniles per cubic meter and fed with experimental diets including 25, 30, or 35% crude protein for 87 days. The highest mean weight and specific growth rate (SGR) were 39.5 g and 2.13% day -1 , re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Further, it has been reported that some amino acids play a role in osmoregulation (Ballantyne, ), and when the fish are exposed to lower salinity, the level of osmotically active amino acids in serum increases, which might be obtained from the catabolism of protein. Therefore, reduced protein accretion is expected as found in several fish species (Abdel‐Tawwab et al, in Nile tilapia; Gangadhar, Nandeesha, Varghese, & Keshavanath, in rohu; Mohanta et al, in silver barband mullet species, Altunok & Özden, ; De et al, ; De Carvalho et al, ).The RNA:DNA ratio is a reliable parameter of protein synthesis hence signifies fish growth (Steinhart & Eckman, ). DNA is necessary for protein synthesis that remains constant in tissue (Mitra & Mukhopadhyay, ) as found in this study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Further, it has been reported that some amino acids play a role in osmoregulation (Ballantyne, ), and when the fish are exposed to lower salinity, the level of osmotically active amino acids in serum increases, which might be obtained from the catabolism of protein. Therefore, reduced protein accretion is expected as found in several fish species (Abdel‐Tawwab et al, in Nile tilapia; Gangadhar, Nandeesha, Varghese, & Keshavanath, in rohu; Mohanta et al, in silver barband mullet species, Altunok & Özden, ; De et al, ; De Carvalho et al, ).The RNA:DNA ratio is a reliable parameter of protein synthesis hence signifies fish growth (Steinhart & Eckman, ). DNA is necessary for protein synthesis that remains constant in tissue (Mitra & Mukhopadhyay, ) as found in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Further, it has been reported that some amino acids play a role in osmoregulation (Ballantyne, 2001), and when the fish are exposed to lower salinity, the level of osmotically active amino acids in serum increases, which might be obtained from the catabolism of protein. Therefore, reduced protein accretion is expected as found in several fish species (Abdel-Tawwab et al, 2010 in Nile tilapia; Gangadhar, Nandeesha, Varghese, & Keshavanath, 1997 in rohu;Mohanta et al, 2008 in silver barband mullet species, Altunok & Özden, 2017;De et al, 2012;De Carvalho et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since a long time, there has been a large interest in studies concerning mugilids and a diversity of subjects. These have included the biology of the mullets (De Silva, 1980;Crosetti and Cataudella, 1995;Whitfield et al, 2012;Cardona, 2016;González-Castro and Minos, 2016;Ibáñez, 2016), the acclimation of mugilid to low salinities (Chervinski, 1977;Nordlie et al, 1982;El Cafsi et al, 2003;Khériji et al, 2003;Rabeh et al, 2010Rabeh et al, , 2015Nordlie, 2016) the development of the early stages (Zouiten et al, 2008;Ben Khemis et al, 2013;Koutrakis et al, 2016), or the pollution and biomonitoring (Waltham et al, 2013) or stock enhancement and fisheries (Losse et al, 1991;Vidy and Franc, 1992;Crosetti, 2016;Leber et al, 2016) in the environments where they occur as well as aquaculture (Nash and Shehadeh, 1980;El-Sayed, 1991;Ben Khemis et al, 2006;Besbes et al, 2010;Crosetti, 2016;Gisbert et al, 2016;Altunok and Özden, 2017). Reviews on different topics related to biology, ecology and culture of grey mullet taxonomy have been compiled recently in a book edited by Crosetti and Blaber (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thinlip grey Mullet (Liza ramada) originated in the Mediterranean and is a valuable fish species for aquaculture in Egypt (El-Sharawy et al, 2021). In several European countries, mullets have become promising fish candidates for aquaculture associated of their high tolerance to brackish water conditions and omnivorous feeding habits (Altunok and Özden, 2017). Plant protein ingredients are increasingly included in mullet feeds and are expected to be contaminated with mycotoxins (AFB1).…”
mentioning
confidence: 99%